Identification of antiviral RNAi regulators, ILF3/DHX9, recruit at ZIKV stem loop B to protect against ZIKV induced microcephaly - Zhiwei Lei; Yu Gu; Ying Liu; Hailiang Liu; Xiaohua Lu; Weijie Chen; Lu Zhou; Pan Pan; Zhuohong Chen; Zhaoyang Yue; Jinhui Ruan; Leqing Zhu; et al. (Nature Communications)
Abstract Zika virus (ZIKV) is a member of the Flaviviridae family and causes congenital microcephaly and Guillain–Barré syndrome. Currently, there is a lack of approved vaccines or therapies against ZIKV infection. In this study, we profile vRNA‒host protein interactomes at ZIKV stem‒loop B (SLB) and reveal that interleukin enhancer binding factor 3 (ILF3) and DEAH-box helicase 9 (DHX9) form positive regulators of antiviral RNA inference in undifferentiated human neuroblastoma cells and induced pluripotent stem cell-derived human neural stem cells (iPSC–NSCs). Functionally, ablation of ILF3 in brain organoids and Nestin-Cre ILF3 cKO foetal mice significantly enhance ZIKV replication and aggravated ZIKV-induced microcephalic phenotypes. Mechanistically, ILF3/DHX9 enhance DICER processing of ZIKV vRNA-derived siRNAs (vsiR-1 and vsiR-2) to exert anti-flavivirus activity. VsiR-1 strongly inhibits ZIKV NS5 polymerase activity and RNA translation. Treatment with the vsiR-1 mimic inhibits ZIKV replication in vitro and in vivo and protected mice from ZIKV-induced microcephaly. Overall, we propose a novel therapeutic strategy to combat flavivirus infection.